High Grade (Large Cell) Neuroendocrine Carcinoma of the Nasopharynx: Novel Case Report with Touch Preparation Cytology and Positive EBV Encoded Early RNA. (10th May 2015) - Sturgis, Charles D.; Burkey, Brian B.; Momin, Suhael; Hoschar, Aaron P.
Abstract : Fewer than five case reports of primary large cell neuroendocrine carcinoma of the nasopharynx are known to the authors. No previous reports have included examples of cytomorphology or have proven association with Epstein-Barr virus. We herein illustrate MRI findings, histopathologic features, immunohistochemical characterization, cytologic details, and in situ hybridization studies from a unique case of primary large cell neuroendocrine carcinoma of the nasopharynx in a 38-year-old Caucasian male patient. Recognition of rare tumor types of the nasopharynx allows for refinements in disease management and prognostication.